The Association between Interleukin-6 and Mean Platelet Volume Levels in Central Obesity with or without Non-Alcoholic Fatty Liver Disease - Linda Rotty; Nelly Tendean; Nancy Lestari; Randy Adiwinata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Obesity had become a global problem today. Obesity is a significant risk factor of cardiovascular and other metabolic diseases such as non-alcoholic fatty liver disease (NAFLD). It remains unclear if the increased mean platelet volume (MPV) at the steatosis state is practicable as early detection of the occurrence of fatty liver in individuals with central obesity. This study aims to determine the association of interleukin-6 (IL-6) and MPV levels in central obesity with or without NAFLD.Method: This study was descriptive-analytic with a cross-sectional approach conducted in Prof. dr. R. D. Kandou Manado general hospital from May to July 2018. Consecutive sampling was performed based on inclusion criteria, then IL-6, MPV, and abdominal ultrasound examinations were performed.Results: This study included 40 samples of men with central obesity, 28 people (70%) among them were diagnosed with NAFLD. The Fisher exact test showed an association between NAFLD and an increase in IL-6 (p = 0.039), also between MPV and NAFLD (p=0.015). Pearson correlation test showed there was no significant correlation between IL-6 and MPV in the NAFLD sample group (p = 0.084; r -0.332) and in the non-NAFLD sample group (p = 0.564; r -0.186).Conclusion: Elevated MPV and IL-6 values may be used as marker for NAFLD presence among central obesity patients.